We drink from our own wells : the spiritual journey of a people - Gutiérrez, Gustavo, 1928- (Quezon City Claretian Publications, 1984)
In search of God - Joy - Spiritual childhood
"Foreword by Henri Nouwen with a new introduction by the author"--Cover
Includes bibliographical references and indexes
Keywords: Spiritual life -- Christianity; Church work with the poor -- Latin America; Latin America -- Religious life and customs; Latin America -- Economic conditions -- 1945-